Kesendirian dan Celebrity Worship pada Penggemar K-Pop Perempuan Emerging Adulthood - Megale, Ivena; Susilo, Dicky (Psychopreneur Journal, 2024)
Abstract. Celebrity worship is a relationship that a person builds with continuous effort and full focus to the point of obsession and attachment to a particular artist. This phenomenon occurs because there are a lot of exciting artists and media content with easy access via the internet. One of the factors that influence celebrity worship is the loneliness. This research aims to see whether there is a relationship between loneliness and celebrity worship among female K-Pop fans in emerging adulthood. The sampling used was purposive sampling and incidental sampling. The measuring instrument used is the celebrity worship and loneliness scale (SELSA-S). The results of the hypothesis test obtained a value of r = -0.024 (p> 0.05), so it can be concluded that there is no relationship between loneliness and celebrity worship among emerging adulthood female K-Pop fans. The absence of a relationship between the two variables occurs due to the social support received when being a K-Pop, so one does not experience loneliness. Keywords: Loneliness, Celebrity Worship, Emerging Adulthood, Female.